Induction of Chromosomes Aberration and Micronucleus by Glyphosate Herbicide in Bone Marrow Cell of Male Mice Mus Musculus - W. Ahmed , Faizah (University of Thi-Qar Journal of Science, 2015)
The present study was designed to investigate the ability of the herbicide Glyphosate to induce cytogenetic effectsin the laboratory mice Mus musculus, using chromosomal aberration and micronucleus parameters. Mice wereintraperitoneally (i.p) injection with 12.5, 25 mg/kg of Glyphosate for two periods 15 and 30 days. The result showedthat Glyphosate caused significant increase in the chromosomal aberration , ring chromosome , centromeric break and chromatid break in comparison with the control group .The higher dose induced chromosomal aberration at significant level (P<0.01) compared with the lower does . Injection of Glyphosate for 30 days caused significant increase chromosomal aberration in the experimental group compared with control group. Glyphosate injection induced micronucleus .There was a significant increase caused by the higher dose compared with lower dose for the two periods 15 and 30 days .